2016
DOI: 10.1021/acs.orglett.6b00699
|View full text |Cite
|
Sign up to set email alerts
|

Dithiane Induced Cycloaddition/Aromatization Tactic for the Synthesis of Multisubstituted Furans

Abstract: The development of a new transition-metal-free tactic for convergent, one-pot synthesis of multisubstituted furans by β-chloro-vinyl dithiane cyclization with aldehydes is described. Key to the success was the development of a new vinylidene dithiane site as a donor allene that generates the active dihydrofuran, which undergoes in situ aromatization under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 50 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Among various types of organic reagents, dithiane compounds serve as valuable umpolung intermediates in the field of synthetic organic chemistry because of their unique properties and reactivities. Recently, the demonstrated ambivalent donor–acceptor (D–A) reactivities of β-chlorovinyl dithianes in our group have opened up a novel class of reaction pathways beyond the typical dithiane methods . The development of [3 + 2]-cycloaddition has been achieved through identification of reactive vinylidene dithiane species and aldehydes .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Among various types of organic reagents, dithiane compounds serve as valuable umpolung intermediates in the field of synthetic organic chemistry because of their unique properties and reactivities. Recently, the demonstrated ambivalent donor–acceptor (D–A) reactivities of β-chlorovinyl dithianes in our group have opened up a novel class of reaction pathways beyond the typical dithiane methods . The development of [3 + 2]-cycloaddition has been achieved through identification of reactive vinylidene dithiane species and aldehydes .…”
mentioning
confidence: 81%
“…Our investigations commenced with the cyclization of equimolar amounts of β-chlorovinyl dithiane 1a and chalcone 2a under the previously reported conditions . As shown in Table , we found promising results when employing an excess amount of base (3.0 equiv t -BuOK in DMSO).…”
mentioning
confidence: 99%
“…[8] Our research group has demonstrated the potential transformations of β-chlorovinyl dithianes with unsaturated compounds for the synthesis of highly substituted 1,3-dithianes, which are versatile umpolung acyl building blocks in organic synthesis. [9] Based on previous studies, [10] it has been shown that the dithianyl ring opening of the vinyl dithianes results in a vinyl- thionium ion under acidic conditions that could directly engage in CÀ C bond formation with a range of nucleophilic reagents and alkenes. With this in mind, we focused on developing a set of transition-metal-free conditions for the straightforward synthesis of highly dithianyl substituted dienes by exploiting the Lewis acid-promoted cross-coupling of β-chlorovinyl dithianes and alkenes (Scheme 1d).…”
mentioning
confidence: 99%